The Influence of Green Human Resource Management Practices and Green Inclusive Leadership on Green Competitive Advantage and Sustainable Business Performance in SMEs in Madura - Amir Furqon; Ria Rachmawati; Nur Laili; Diana Afriliana; Ayunida Retno Megarani (Majapahit Journal of Islamic Finance and Management, 2025)
This study examines the impact of Green Human Resource Management (GHRM) practices and Green Inclusive Leadership (GIL) on Sustainable Business Performance (SBP), specifically focusing on their effects in SMEs in Madura. The research explores the role of Green Skill Competencies (GSC), Green Creative Self-Efficacy (GCSE), and Green Competitive Advantage (GCA) as mediators in enhancing business performance through green practices. A quantitative approach was employed, utilizing survey data from 497 SME managers in Pamekasan and Bangkalan, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. This study addresses a gap in understanding how green HR practices and leadership styles contribute to the development of green competencies and creative self-efficacy, which, in turn, strengthen green competitive advantage and sustainable business performance. The findings reveal significant positive effects of GHRM and GIL on GSC, GCSE, GCA, and SBP, indicating that integrating green leadership and human resource practices into business strategies can significantly enhance sustainability performance in SMEs. This research contributes valuable insights for policymakers and practitioners seeking to improve business sustainability through green management strategies.